2019
DOI: 10.1021/acsbiomaterials.8b01113
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Eight Sulfated Polysaccharides Extracted from Red and Brown Algae and Its Impact on Structure and Pharmacological Activities

Abstract: Degradation represents a strategy to improve the biopharmaceutical properties of native algae sulfated polysaccharides (SP) with high M w. The aim of this study was to compare the degradability of four sulfated xylogalactans (SXG) and four fucose-rich sulfated polysaccharides (FRSP) extracted from red and brown algae, respectively, using three simple methods causing no desulfation as well as to examine the chemical and pharmacological changes of the resulting fractions. The achieved degradation proved to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The association between fucose content and DS was shown to be due primarily to the fact that the fucose units in fucoidans are sulfated [ 31 ]. In line with previous results [ 27 , 28 ], the treatment at 120 and 100 °C, respectively, was associated with degradation of the fucoidans, but not desulfation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association between fucose content and DS was shown to be due primarily to the fact that the fucose units in fucoidans are sulfated [ 31 ]. In line with previous results [ 27 , 28 ], the treatment at 120 and 100 °C, respectively, was associated with degradation of the fucoidans, but not desulfation.…”
Section: Discussionsupporting
confidence: 92%
“…Crude fucoidan extracts are multicomponent products and their complex composition impede the structure–function correlations. As numerous studies have shown, the biological properties of fucoidans are highly dependent on their chemical properties, which in turn are tightly related to the species as well as the way they are harvested and extracted [ 11 , 26 , 27 , 28 ]. In this study, we evaluated six crude fucoidan extracts from three Fucus species obtained by different extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the overall only small effects of the fucoidans on the cell viability, its impact was only observed in those three cell lines with the largest fucoidan-dependent variability. This may be also the reason for missing correlations between the cell viability and other parameters such as the molecular weight (data not shown), although that is generally considered an important parameter for the biological activities of fucoidans [15,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 5 and 8 represent sulfated xylogalactans from red algae, compounds 6 and 7 are brown algae-derived fucoidans. They were extracted, purified and chemically characterized as previously described [ 32 , 33 , 34 ]. The chemical characteristics of the used batches are shown in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The sulfated polysaccharides 5 – 8 were isolated from the two brown algae Saccharina latissima (Laminariales, Laminariaceae) (North Atlantic Faroe Island) and Fucus vesiculosus (Fucales, Fucaceae) and the two red algae Delesseria sanguinea (Ceramiales, Delesseriaceae) and Coccotylus truncatus (Gigartinales, Phyllophoraceae) (both collected in the sublittoral habitat of the large artificial reef near Nienhagen (Baltic Sea, Germany). They were extracted, purified and chemically characterized as previously described [ 32 , 33 , 34 ], whereby compound 7 , fucoidan from Fucus vesiculosus was purchased from Sigma-Aldrich, catalog No. F5631, Lot No SLBC4004 V).…”
Section: Methodsmentioning
confidence: 99%